2006
DOI: 10.1111/j.1399-6576.2006.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic post‐thoracotomy pain: a retrospective study

Abstract: Our study confirms that chronic post-thoracotomy pain is a common problem. The results from our study suggest that chronic post-thoracotomy pain may be associated with more intensive and extensive nociceptive input due to thoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(99 citation statements)
references
References 16 publications
6
85
2
2
Order By: Relevance
“…1,[4][5][6][7] The International Association for the Study of Pain defines PTPS as pain that recurs or persists along a thoracotomy scar longer than 2 months after surgery. 2,[4][5][6][7][8][9][10][11] The syndrome is thought to be predominantly of neuropathic origin, 1,9,12 secondary to damage to the intercostal nerves, causing neuralgia, but also caused by myofascial pain. 13 Many risk factors have been implicated and include genetic susceptibility, young age, female sex, pain before surgery, severe acute postoperative pain, and high postoperative opioid consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[4][5][6][7] The International Association for the Study of Pain defines PTPS as pain that recurs or persists along a thoracotomy scar longer than 2 months after surgery. 2,[4][5][6][7][8][9][10][11] The syndrome is thought to be predominantly of neuropathic origin, 1,9,12 secondary to damage to the intercostal nerves, causing neuralgia, but also caused by myofascial pain. 13 Many risk factors have been implicated and include genetic susceptibility, young age, female sex, pain before surgery, severe acute postoperative pain, and high postoperative opioid consumption.…”
Section: Methodsmentioning
confidence: 99%
“…13 Many risk factors have been implicated and include genetic susceptibility, young age, female sex, pain before surgery, severe acute postoperative pain, and high postoperative opioid consumption. 1,4,6,[14][15][16] Mechanisms leading to PTPS and other chronic postoperative pain syndromes are not well understood. It is suggested that intense nociceptive stimulation activates N-methyl D-aspartate receptors, and opioid-induced hyperalgesia after the use of highdose opioids leads to wind-up, facilitation, central sensitization, and long-term potentiation.…”
Section: Methodsmentioning
confidence: 99%
“…All of these factors can be linked to altered pain processing. Lower age, consistently associated with higher incidences of chronic postoperative pain, may be associated with a more vigorous neuroplastic response, whereas gender-dependent differences in pain modulation are now well described in the literature (3,4,7,8,10,(12)(13)(14)(15)(16)(17)(18). Surgery-related factors linked to increased incidences of chronic pain after surgery, including more preoperative pain, more pain and higher analgesia consumption in the early postoperative period, more extensive surgery, and nerve damage have increased pain sensitivity in common, in that these factors can all be either expressions of hyperalgesia (more preoperative or postoperative pain, more postoperative analgesia consumption), or a cause thereof (nerve damage, more extensive surgery) (3, 4, 7, 8, 10-12 18-25).…”
Section: Clinical Risk Factors For Chronic Pain After Surgery and Altmentioning
confidence: 97%
“…16,17 In the study, we also found that acute postoperative pain after thoracotomy was an independent risk factor for the development of CPTP. This was not consistent with the reports of Perttunen et al 18 The primary cause of this difference may be associated with the study design, such as significant recall bias in retrospective investigations or using analgesic consumption as an indirect measurement instead of the acute pain scores immediately after surgery.…”
Section: Discussionmentioning
confidence: 83%